Bipyridine-triggered modulation of structure and properties of zinc-diphosphonates: coordination role vs. template rule. Issue 5 (12th January 2018) - Ma, Yu-Juan; Han, Song-De; Mu, Ying; Pan, Jie; Li, Jin-Hua; Wang, Guo-Ming
Abstract : Two layered zinc-diphosphonates driven by 4, 4′-bipy are prepared and their structural diversities are caused by the distinct roles of 4, 4′-bipy in the process of assembly. The luminescence and proton conduction are studied. Abstract : Two zinc-diphosphonates driven by 4, 4′-bipyridine (4, 4′-bipy), [Zn4 (HEDP)2 (4, 4′-bipy)2 ]·4.5(H2 O) (1 ) and (H2 -4, 4′-bipy)0.5 ·[Zn3 (HEDP)(H2 EDP)(H2 O)]·1.5(H2 O) (2 ), were solvothermally prepared (HEDP = CH3 C(OH)(PO3 )2, 1-hydroxyethylidenediphosphonate). Compound1 features a layered structure with the Zn-HEDP chains as supramolecular units and 4, 4′-bipy as interchain linkers. Compound2 possesses a Zn-HEDP layer with protonated 4, 4′-bipy as template. The structure differences between the two compounds are mainly ascribed to the distinct role of 4, 4′-bipy in the process of in situ assembly. In compound1, the 4, 4′-bipy moiety acts as coordinative unit to participate in the formation of the resulting architecture. However, in compound2, the protonated 4, 4′-bipy serves as template to direct the formation of the final structure. The luminescence and proton conduction of the two compounds were investigated. Compounds1 and2 exhibit intense blue fluorescence; compound2 has a proton conductivity of 2.61 × 10 −4 S cm −1 at 100% relative humidity and 70 °C.